DEVELOPMENT OF FISH BODY ORGAN LEARNING MEDIA FOR CLASS V STUDENTS IN ELEMENTARY SCHOOL - Setiyawan, Yogi; Reffiane, Fine; Agustini, Ferina (Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
This research is conducted by observation that shows that there is still lack of science learning media that explain the organ material in this case is the material of breathing tool of fish. Difficulties of students in understanding the material also become a consideration by researchers to development media board organ tray fish body. This type of research is a research and development method or Research and Development (R & D). The development of fish board tray board boards consists of five stages: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. From the fifth step is produced media board tray organ organs of fish. The media products of fish body tray board trays are developed and validated by experts. Results The products and materials from two experts showed the percentage score of 90.38% in the